Building Children's Spiritual Intelligence Through Education in the Family - Khoiri Khoiri (Madrosatuna: Journal of Islamic Elementary School, 2022)
Humans have multiple intelligences, one of the human intelligence that significantly determines the success and safety of his life is Spiritual Intelligence. Spiritual Intelligence was coined by a physicist from Oxford University named Marshall after years of research. After that, scientific evidence about Spiritual intelligence was found successively by experts in other fields. Like other intelligence, Spiritual intelligence can also be trained, honed, and sharpened through education. Thus, because the environment first known by humans is the family, the family is most likely to take on the role of Spiritual intelligence education. The steps for Spiritual Intelligence education have also been formulated by education experts, including education experts in Indonesia, including by taking steps including 1) Zero Mind Process, 2) Mental Building, 3) Personal Strength, and 4) Total Application. This research is library research, utilizing library sources to obtain data and research. Library research is limited to library collection materials without the need for field research.